2012
DOI: 10.1021/om3003575
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Emission Characteristics, Cellular Studies, and Bioconjugation Properties of Luminescent Rhenium(I) Polypyridine Complexes with a Fluorous Pendant

Abstract: In this article, we report the photophysical and biological properties of new luminescent rhenium­(I) polypyridine fluorous complexes. The complexes [Re­(N∧N)­(CO)3(py-Rf-NH2)]­(PF6) (py-Rf-NH2 = 3-amino-5-(N-((3-perfluorooctyl)­propyl)­aminocarbonyl)­pyridine; N∧N = 1,10-phenanthroline (phen) (1a), 3,4,7,8-tetramethyl-1,10-phenanthroline (Me4-phen) (2a), 4,7-diphenyl-1,10-phenanthroline (Ph2-phen) (3a)) contain a fluorous pendant and a primary amine for modification. They have been converted to the isothiocya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 84 publications
1
24
0
Order By: Relevance
“…This is generally done by tuning the structure of the N^N ligand, since it is involved in the MLCT. Two families of ligand have been particularly explored: (i) polypyridyl ligands, mostly derived from 2,2'-bipyridine (bpy) and 1,10-phenanthroline (phen) [19][20][21][23][24][25][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] and (ii) bis-quinoline and its derivatives, e.g. bis(phenanthridinylmethyl)amine (bpm) [22,[43][44][45].…”
Section: Spectroscopic Properties Of Luminescent Re(i) Tricarbonyl Comentioning
confidence: 99%
“…This is generally done by tuning the structure of the N^N ligand, since it is involved in the MLCT. Two families of ligand have been particularly explored: (i) polypyridyl ligands, mostly derived from 2,2'-bipyridine (bpy) and 1,10-phenanthroline (phen) [19][20][21][23][24][25][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] and (ii) bis-quinoline and its derivatives, e.g. bis(phenanthridinylmethyl)amine (bpm) [22,[43][44][45].…”
Section: Spectroscopic Properties Of Luminescent Re(i) Tricarbonyl Comentioning
confidence: 99%
“…Due to the luminescent nature of the complexes, the authors were also able to monitor uptake in live cells via confocal microscopy, and even observe the localization of the complexes in the mitochondria of the cells. 63 …”
Section: Cellular Uptake Of Metal Complexesmentioning
confidence: 99%
“…63 Using ICP-MS, the authors were able to correlate the cytotoxicities of these complexes in HeLa cells with intracellular rhenium concentrations. Using fluorescence microscopy (bottom), the authors were able to observe the localization of one such complex (structure shown in bold, fluorescence shown on bottom left in red) in HeLa cells.…”
Section: Figurementioning
confidence: 99%
“…The recent observation [28] of enhanced fluorophilicity of species functionalised with perfluoropolyether groups over those with perfluoroalkyl groups is a clear signpost of a direction to be followed in organometallic chemistry. Secondly, insight is provided by the recent work on the engineering of organometallic systems in which the fluorous substituent imparts specific, even unique, biological properties to the organometallic complex [79][80][81], and this is undoubtedly an area that is going to grow in the next few years. We look forward to the continued evolution of research in fluorous organometallic chemistry.…”
Section: Fluorous Organometallic Chemistrymentioning
confidence: 99%
“…These compounds with fluorous tails show greater uptake by tumoral cells than analogues with long alkyl tails and are thermoresponsive, exerting considerable chemotoxicity on mild hyperthermia. Three luminescent rhenium(I) bipyridyl complexes [Re (CO) 3 [81], prepared by displacement of acetonitrile from the parent organometallic complexes, have been investigated as trifunctional biological probes that have luminescent properties for detection and a reactive group for bioconjugation and exploit the perfluoroalkyl functionalisation for straightforward isolation using fluorous solid-phase extraction.…”
Section: Introductionmentioning
confidence: 99%